Sliding mode control of vehicle dynamics - Ferrara, Antonella (IET transportation series ;, 2017)
The book reviews developments in the following fields: sliding mode control; longitudinal vehicle dynamics control; sliding modes generation; traction control; braking control; two-wheeled vehicles; lateral vehicle dynamics control; stability control; heavy vehicles; semi-active suspension control; observer-based parameter identification; and vehicle dynamics assessment.